Microstructural analysis of novel Gd2Ti2O7 thin films processed via sputter deposition. (1st February 2021) - Derby, Benjamin K.; Holesinger, Terry G.; Valdez, James A.; Uberuaga, Blas P.; Kreller, Cortney R.
Abstract: Complex oxides, such as Gd2 Ti2 O7, are potential candidates for energy-transport materials in advanced technological applications and nuclear waste forms. Microstructural features such as crystallinity and interface structure ultimately determine the transport characteristics in these materials. In the present study, a microstructural analysis was completed by transmission electron microscopy of Gd2 Ti2 O7 thin films exposed to different synthesis conditions to determine these conditions' effects on the resultant morphology. The Gd2 Ti2 O7 thin films were prepared by a sputter-deposition technique using Ar and O2 mixed process gas. The film structure was found to be sensitive to process gas pressure and substrate temperature during sputtering based on two different choices in process gas pressures and four different choices in substrate temperatures. Amorphous Gd2 Ti2 O7 thin films with a unique, dyadic void network were synthesized at substrate temperatures at and below 600 °C and relatively low process gas pressures of 2.7 Pa. Single crystal Gd2 Ti2 O7 thin films were synthesized at 800 °C and 4 Pa. While the temperature-dependent film morphology that was observed has been seen in a number of other systems, this is the first report generalizing this behavior to complex oxides. The resultant thin film morphologies are rationalized via an adatom mobility description. Graphical abstract: Unlabelled Image Highlights: Increasing the thermal energy of GTO adatoms to 0.57 homologous temperature during growth produced a single-crystal GTO film. Voids present after low-temperature growth impedes the development single-crystal, GTO thin films. When defect kinetics are sluggish, a metastable GTO microstructure develops instead of the equilibrium pyrochlore structure.